Quantificação de elementos potencialmente tóxicos em sombras para olhos - Zeppini, Anna Claudia Tocchio (Universidade Federal de São Carlos, 2025)
The presence of potentially toxic elements in cosmetics, especially in eye shadows, is an increasing concern due to the health risks associated with these elements. Metals such as cadmium (Cd), chromium (Cr), nickel (Ni), and lead (Pb), which are often used in metallic pigments, can exceed safety limits, causing irritation, dermatitis, and, in cases of prolonged exposure, systemic toxicity. Strict regulation of raw materials and manufacturing processes is crucial to ensure consumer safety. Studies on the composition of cosmetics are essential to improve regulations and mitigate health risks. In this context, this study aimed to quantify Cd, Cr, Ni, and Pb in samples of eye shadows from different brands and shades, as well as to discuss the potential health effects on users. The samples were subjected to microwave-assisted digestion and then quantified by Microwave Plasma-Atomic Emission Spectrometry (MP-AES). The results indicated that while Cd, Ni, and Pb were below the detection limits, Cr was found in concentrations above the limit set by ANVISA (1 ppm) in all samples, particularly in more intense shades like brown and wine. The findings may be associated with quality control failures in manufacturing and high light concerns about contamination, considering the health risks. Therefore, it is recommended to implement more effective quality control measures and strengthen regulation.
Quantification of potentially toxic elements in eye shadows
Keywords: Cosméticos; Pigmentos metálicos; Controle de qualidade; Sombra de olhos; Riscos à saúde; Cosmetics; Metallic pigments; Quality control; Eye shadows; Health risks; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL